Treatment of Depression in Integrated Care: Implementation of the Nurse Care Manager - Elizabeth G. Adams MSN, CNL, PHN (SAGE Open Nursing, 2019)
The collaborative care model is an effective model for improving depression symptoms in patients in a primary care (PC) setting. An essential role in this model is the care manager (CM), and nurses have been effective in this role. However, there remains a question of how to best design, train, and implement this nurse CM role in PC. The purpose of this review is to provide readers with a critical description of what processes for training and implementation of a collaborative nurse CM role have been be successful in the literature, specifically as it pertains to supporting patients with depression and chronic medical illnesses in an integrated PC setting. A literature review of PubMed, CINAHL, PsychINFO, Scopus, and the Cochrane Collaborative was conducted in October 2018. Successful nurse CM interventions have included regular patient follow-up, symptom check-in, treatment monitoring, goal setting, and education. Psychological support techniques such as Problem-Solving Therapy, behavioral activation, and motivational interviewing have been useful in supporting patient care-plan engagement and goal achievement. Nurse CM training should support the successful implementation of the designed role. Nurse CMs have an opportunity to significantly impact depressive outcomes of patients with depression and long-term health conditions. Further research is needed to explore the potential that this nursing role has as well as how to best operationalize this role.